Synthesis of Activated Carbon from Dragon Fruit Peel for Adsorption of Methyl Blue - Tran, Thi Ngoc Diem; Tran, Thi Tuu; Hoang, Bich Ngoc; Lam, Van Tan; Ngo, Thi Cam Quyen (Universitas Gadjah Mada, 2024)
In this study, activated carbon from dragon fruit peel was synthesized and applied for its ability to adsorb organic pigments in water. The results obtained from the SEM and FTIR analyzes revealed the presence of the characteristic functional groups of activated carbon. The adsorption capacity of synthetic activated carbon was evaluated against methylene blue dye. This study also evaluated factors affecting the adsorption process, including time, content, temperature, concentration, and solution pH. The optimal adsorption conditions were recorded at pH 6, concentration 95 mg/L, time 43 min, and temperature 30 °C. At optimal adsorption conditions, the adsorption capacity predicted from the model is said to be 54.12 mg/g with an efficiency of 27.5%. The experimental data of the study were evaluated using adsorption kinetic models and adsorption isotherm models of the material. The results showed that the activated carbon material from dragon fruit peel is a potential material in the application for adsorbing pollutant dyes in wastewater.